Memory B cells in the lung participate in protective humoral immune responses to pulmonary influenza virus reinfection - Onodera, Taishi; Takahashi, Yoshimasa; Yokoi, Yusuke; Ato, Manabu; Kodama, Yuichi; Hachimura, Satoshi; Kurosaki, Tomohiro; Kobayashi, Kazuo (Proceedings of the National Academy of Sciences - PNAS, 2012)
After pulmonary virus infection, virus-binding B cells ectopically accumulate in the lung. However, their contribution to protective immunity against reinfecting viruses remains unknown. Here, we show the phenotypes and protective functions of virus-binding memory B cells that persist in the lung following pulmonary infection with influenza virus. A fraction of virus-binding B-cell population in the lung expressed surface markers for splenic mature memory B cells (CD73, CD80, and CD273) along with CD69 and CXCR3 that are up-regulated on lung effector/memory T cells. The lung B-cell population with memory phenotype persisted for more than 5 mo after infection, and on reinfection promptly differentiated into plasma cells that produced virus-neutralizing antibodies locally. This production of local IgG and IgA neutralizing antibody was correlated with reduced virus spread in adapted hosts. Our data demonstrates that infected lungs harbor a memory B-cell subset with distinctive phenotype and ability to provide protection against pulmonary virus reinfection.